Ще раз про обряд поховання носіїв роменської культури - Бібіков, Д.В. (Археологія і давня історія України, 2021)
Стаття присвячена всебічному аналізу поховального обряду роменської культури та окремих його елементів. The study of the funeral rite of the Eastern Slavs and the dynamics of its development is important for the clarification of the religious, state-creating, ethnocultural and social processes of the Old Rus formation. In the paper the author makes a new attempt of the comprehensive analysis of the burial sites of chronicle Severians who are identified with the bearers of Romenska archaeological culture. For this purpose, the most complete and reliable catalogue of these sites included 142 items has been created. Statistical calculations show at the main part of the Dnieper Left Bank in the 9th—10th centuries the dominance of cremation rites away from the burial, placing the urn in the upper levels of the mound. Burials of this type are at least 82 % of Romenska culture cremations. They are reflected in literary sources. Burials at the level of the horizon and in small holes should be considered only as a few deviations from the classical Romenski rite. Burials of these types are characterized by such specific elements as circular wooden fences and ritual hearths, and most of them do not contain the urns. Differences in the funeral rites of the Dnieper Left Bank can be explained by the reasons of both ethnographic and chronological nature. In the second half of the 10th century in the Severians area a few cremations are recorded at the places of burial. No Romenska culture pottery or ornaments were found in any of these complexes: they all contained exclusively the Old Rus materials. There is no doubt that the rite of cremation at the place was brought to the Dnieper Left Bank by settlers from the Middle Dnieper together with the establishment of the Kyiv Princes power. Radical changes in the Romenski funeral rite occur in the late 10th — early 11th centuries. The rite of inhumation at the level of the horizon becomes dominant, less often in the mound pits. Although a number of scholars link these changes to the socio-economic changes in society the author considers it possible to explain them only by the total Christianization of the newly acquired territories by Kyiv. It is likely that the cremation of the dead was strictly forbidden by the church.